A novel approach in the treatment of osteoarthritis: In vitro and in vivo evaluation of Allium sativum microemulsion. Issue 5 (20th June 2022) - Okur, Mehmet Evren; Kolbaşı, Bircan; Şahin, Mustafa; Karadağ, Ayşe Esra; Reis, Rengin; Çağlar, Emre Şefik; Kaplan, Arife Ahsen; Sipahi, Hande; Keskin, İlknur; Demiralp, Bahtiyar; Üstündağ Okur, Neslihan
Abstract: Osteoarthritis (OA) is the most prevalent kind of joint disease, affecting millions of individuals worldwide. Allium sativum L . was used as a therapeutic agent in the microemulsion system against osteoarthritis due to allicin's high antioxidant and anti‐inflammatory effects. HPLC was used to evaluate the chemical components of the Allium sativum methanol extract. Water‐in‐oil (w/o) type of microemulsions loaded with Allium sativum extract was produced. To create the microemulsions, a titration approach was employed. The microemulsions were prepared using isopropyl myristate (IPM) as oil, Polysorbate 60, Sorbitan monolaurate 80 as surfactants, and Polyethylene glycol 400, ethanol as cosurfactants. The pH, droplet size, viscosity, polydispersity index values were measured to characterize of microemulsions. In addition, L929 healthy mouse fibroblasts and CHON‐001 healthy human cartilage fibroblast cells were tested for cytocompatibility in vitro. The therapeutic potential of Allium sativum microemulsion was investigated in rats that had osteoarthritis surgically simulated. HPLC analysis revealed a significant concentration of allicin in the extract. The titration approach was used to create an A. sativum microemulsion (AS) with a narrow droplet size and PDI range. In L929 and CHON‐001 cells, cytocompatibility experiments revealed that the maximum dosages of AS microemulsion 5% (v/v) exerted 93.41 ± 3.11% and 75.59 ±2.69% cell viabilities, respectively. Different concentrations of AS (1.25%, 2.5%, and 5% v/v) demonstrated cytoprotective efficacy against H2 O2 ‐induced oxidative damage. When compared to the control group, in vivo investigations revealed fewer irregularities on the articular surface and typically arranged chondrocytes in the positive control and treated groups.